Production of probiotic Streptomyces biomass from starchy wastewater - Suteera Srisamai (2018)
Ten probiotic Streptomyces strains isolated from soils and fish intestines were cultured in starchy wastewater collected from the potato chip factory in northern Thailand. Among these, 8 isolates were able to grow in starchy wastewater as sole source of nutrient and yielded equivalent growth as those cultivated in synthetic medium; Yeast extract protein starch soluble (YpSs) under the same condition (150 rpm at 30°C for 7 days). Two Streptomyces, F7-6 and F8-6 were chosen for time course experiment in starchy wastewater. The highest growth was observed on day 4 of cultivation with biomass yield of 3.855±0.32 mg/ml and 2.766±0.63 mg/ml, respectively.